Paradigma Keilmuan Manajemen Pendidikan Islam - Irawan Irawan (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
When the word “Islam” is attached to the subject “Education Management” and become “Islamic Education Management” it would rise a question whether or not it is a science? If It is a science, what is the assurance that truly represent it as a science? This paper tries to proof that Islamic education management could be considered as a science and it bears its own scientific paradigm. The analysis employs the critical realism school of Stephen Ackroyd in the philosophy of management as well as numbers of episthemeological issues of organizational practices by Frits Schipper that are brought to the context of Islamic education. The analysis shows that the formal object of Islamic education management is management science, whereas, its material object is management practices of educational activities in Islamic education institutions such as madrasah, pesantren (boarding school) dan Islamic schools. The researches in Islamic education management focus on facts, context, event and cases happened in that institutions, by not merely attaching Qur’anic verses in the existing theory of education management, so that it looks Islamic, since the Qur’an is also contextual with its asbabun nuzul (the causes of revelation) concept.